RELATIONSHIP BETWEEN TREATMENT ADHERENCE AND PROGRESSION OF DIABETIC NEPHROPATHY - Chua, Jimmy; Firmansyah, Yohanes; Satyanegara, William Gilbert; Santoso, Alexander Halim; Su, Ernawati (Universitas Tarumanagara, 2021)
In 2006, the Indonesian Renal Registry (Pernefri) shows about 12,5% of people in Indonesia suffer from chronic kidney disease. The most common cause of chronic kidney disease in 2018 in Indonesia is 39% by renal hypertension and 22% by Diabetic Nephropathy. This cross-sectional study was conducted at